A comparative analysis of the evolution of imperfect mimicry - Penney, Heather D.; Hassall, Christopher; Skevington, Jeffrey H.; Abbott, Kevin R.; Sherratt, Thomas N. (Nature (London), 2012)
In hoverflies with a small body size, even imperfect Batesian mimicry suffices to limit predation because they are not subject to particularly intense selection. Why hoverflies create a poor impression Batesian mimics are potential prey species that are harmless to predators but gain protection through a resemblance to unpalatable prey species. Surprisingly, many Batesian species seem to be fairly mediocre mimics, despite presumably strong evolutionary pressure to improve the resemblance. This paper presents a morphological and phylogenetic analysis of harmless hoverfly species that mimic — with various degrees of success — stinging hymenopteran species. The authors rule out several hypotheses, such as that the imperfect mimicry is an artefact of human perception and that the imperfect mimics are actually hedging their bets by resembling several hymenopteran species at the same time. Instead, the authors find a link between imperfect mimicry and small body size, which suggests that the imperfect mimics are simply not subject to particularly intense selection. Although exceptional examples of adaptation are frequently celebrated, some outcomes of natural selection seem far from perfect. For example, many hoverflies (Diptera: Syrphidae) are harmless (Batesian 1 ) mimics of stinging Hymenoptera 2 . However, although some hoverfly species are considered excellent mimics, other species bear only a superficial resemblance to their models 3 and it is unclear why this is so. To evaluate hypotheses that have been put forward to explain interspecific variation in the mimetic fidelity of Palearctic Syrphidae we use a comparative approach. We show that the most plausible explanation is that predators impose less selection for mimetic fidelity on smaller hoverfly species because they are less profitable prey items. In particular, our findings, in combination with previous results, allow us to reject several key hypotheses for imperfect mimicry: first, human ratings of mimetic fidelity are positively correlated with both morphometric measures and avian rankings, indicating that variation in mimetic fidelity is not simply an illusion based on human perception 4 ; second, no species of syrphid maps out in multidimensional space as being intermediate in appearance between several different hymenopteran model species, as the multimodel hypothesis 5 requires; and third, we find no evidence for a negative relationship between mimetic fidelity and abundance, which calls into question the kin-selection 6 hypothesis. By contrast, a strong positive relationship between mimetic fidelity and body size supports the relaxed-selection hypothesis 7 , 8 , suggesting that reduced predation pressure on less profitable prey species limits the selection for mimetic perfection.